Implementasi Nilai-Nilai Kedisiplinan Dalam Sistem Kepengasuhan Santri: Studi Kasus Di Pondok Pesantren Bustanul Makmur 2 Banyuwangi - Amelia Putri Silma; Akmal Bagas Hastomo; Rendy Pratama; Fisca Dwiyanti; Tubagus Muhammad Mu’tashim (Pusat Riset dan Inovasi Nasional, 2025)
Islamic boarding schools (pondok pesantren) serve not only as institutions for transmitting religious knowledge but also play a strategic role in shaping the character of students (santri), particularly in the aspect of discipline. This study aims to describe the implementation of disciplinary values within the student care (kepengasuhan) system at Bustanul Makmur 2 Islamic Boarding School, Banyuwangi. The research employs a qualitative approach with a case study design. Data collection techniques include in-depth interviews, participatory observation, and documentation. The findings indicate that the student care system is carried out in a systematic and structured manner through the enforcement of strict rules, habituation of daily routines, and character development programs such as Tafidh, English Day, and EduCamp. Caregivers (pengasuh) play a central role not only in setting the rules but also in serving as role models and consistent supervisors in the implementation of disciplinary values. Through an integrative and holistic approach, the pesantren succeeds in creating an educational environment conducive to forming students who are obedient to rules, responsible, and possess good self-control. This research contributes to a deeper understanding of the importance of a structured student care system in fostering discipline among students in Islamic boarding schools.